2018
DOI: 10.12659/pjr.899626
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of C-Arm Cone-Beam CT-Guided Percutaneous Transthoracic Needle Biopsy of Lung Nodules

Abstract: SummaryBackgroundA systematic review and meta-analysis of all available publications was performed to evaluate the diagnostic accuracy of percutaneous transthoracic needle biopsy (PTNB) using a C-Arm Cone-Beam CT (CBCT) system in patients with lung nodules.Material/MethodsThedatabases of PUBMED, OVID, EBSCO, EMBASE, and China National Knowledge Infrastructure (CNKI) were systematically searched for relevant original articles on the diagnostic accuracy of CBCT-guided PTNB for the diagnosis of nodules in the lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 47 publications
(74 reference statements)
1
19
0
Order By: Relevance
“…CBCT is very expensive and requires a large physical space for the equipment. Therefore, considering the diagnostic yield and patient safety of conventional CT reported in recent studies, which are comparable with those of CBCT, it is preferable to improve existing conventional CT-guided PTNB than to purchase a CBCT system 1 2 3 4 11 12 . We developed the additional laser guidance system to improve the efficacy and safety of conventional CT-guided PTNB.…”
Section: Introductionmentioning
confidence: 99%
“…CBCT is very expensive and requires a large physical space for the equipment. Therefore, considering the diagnostic yield and patient safety of conventional CT reported in recent studies, which are comparable with those of CBCT, it is preferable to improve existing conventional CT-guided PTNB than to purchase a CBCT system 1 2 3 4 11 12 . We developed the additional laser guidance system to improve the efficacy and safety of conventional CT-guided PTNB.…”
Section: Introductionmentioning
confidence: 99%
“…CT-guided percutaneous biopsy and interventional treatment have numerous advantages, such as high accuracy of position, little damage of tissue, little pain of patients, and wide use in clinical practice. [ 1 3 6 ] There is no need to rotate the gantry angle (θ = 0°) for most of the patients, when they undergo needle biopsy guided by CT. But when it needs to turn angles, the author found that it was hard to confirm the right puncture point according to Equation 2.…”
mentioning
confidence: 99%
“…Massive hemothorax is often caused by the injury of intercostal arteries or the pulmonary artery, for which an open or video-assisted thoracoscopic surgery may be required to achieve hemostasis; (III) Air embolism (43,55,64,65): air embolism is an extremely rare complication but may cause cerebral or spinal cord infarction, myocardial infarction, arrhythmia, heart failure, or even death. Once air embolism occurs, the patient should be immediately placed left lateral decubitus or Trendelenburg's position to prevent residual air in left atrium to pass into the systemic circulation; concurrently, 100% oxygen must be administered to the patient to promote the absorption of the air embolus.…”
Section: Complicationsmentioning
confidence: 99%
“…Once air embolism occurs, the patient should be immediately placed left lateral decubitus or Trendelenburg's position to prevent residual air in left atrium to pass into the systemic circulation; concurrently, 100% oxygen must be administered to the patient to promote the absorption of the air embolus. The patient can also be transferred for hyperbaric oxygen treatment; (IV) Needle-tract seeding of tumor cells (17,64,65):…”
Section: Complicationsmentioning
confidence: 99%